IMPLEMENTASI KURIKULUM BERBASIS CINTA DALAM MENINGKATKAN MINAT BELAJAR AKIDAH AKHLAK KELAS VIII DI MTSN 9 JOMBANG - Zuniati, Rani; Abror Rosyidin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research explores educational frameworks that integrate cognitive and affective growth within Islamic schooling. Specifically, the investigation evaluates the application of the Love-Based Curriculum (LBC) and examines its direct influence on the learning motivation of eighth-grade students. Operating under a descriptive-analytical qualitative design, the inquiry gathered insights from key school stakeholders, including the Vice Principal of Curriculum, an Akidah Akhlak instructor, and the students. Information gathered via field observations, participant dialogues, and institutional documents was systematically processed through standard qualitative reduction, data display, and synthesis methods. The empirical evidence demonstrates that LBC execution relies on foundational discipline combined with three core components: embedding core values, instructional role-modeling, and structured reflective sessions. Ultimately, this compassionate methodology fosters superior classroom participation and elevates student concentration. From a scholarly perspective, these insights expand academic discussions regarding student-centered pedagogy in Islamic institutions, while practically offering educators a strategic blueprint to enhance emotional connections during lessons.